### Related

##### true

minimize_lp(-3*x1+x2,...

Calculate

##### true

f:C or A or (not B an...

f,C=false,D=false,A=f...

f,C=false,D=false,A=f...

Calculate

##### true

f:((not a and (not b ...

f,a=false,b=false,c=f...

f,a=false,b=false,c=f...

Calculate

##### true

t1: not a0 and not a1...

t2: not a0 and not a1...

x2: t1 or t2;

Calculate

##### true

f:(a1 and a2);

f,a2=false,a1=false,a...

f,a2=false,a1=false,a...

Calculate

%enumer:true;

ln(2);

Calculate

##### true

centre_right:not a an...

centre_right,d=false,...

centre_right,d=false,...

Calculate

##### true

F0: a2 and a1 and not...

F0, a3=false,a2=false...

F0, a3=false,a2=false...

Calculate

##### true

eq4:(a1 and a2 and a3);

eq4, a0 = false, a1 =...

eq4, a0 = false, a1 =...

Calculate

t1: A and D;

t2: A and C;

t3: A and B ;

Calculate

### true

Run Example
```(%i1)derivabbrev:true ;
(%o1)                                true
(%i2) mainvar: t;
(%o2)                                  t
(%i3) x(t):= r(t)*sin(theta(t));
(%o3)                     x(t) := r(t) sin(theta(t))
(%i4) y(t):=r(t)*cos(theta(t));
(%o4)                     y(t) := r(t) cos(theta(t))
(%i5) xdot(t):= diff(x(t), t, 1);
(%o5)                     xdot(t) := diff(x(t), t, 1)
(%i6) ydot(t):= diff(y(t), t, 1);
(%o6)                     ydot(t) := diff(y(t), t, 1)
(%i7) xdotdot(t):= diff(xdot(t), t, 1);
(%o7)                  xdotdot(t) := diff(xdot(t), t, 1)
(%i8) ydotdot(t):= diff(ydot(t), t, 1);
(%o8)                  ydotdot(t) := diff(ydot(t), t, 1)
(%o9)                 thetadot(t) := diff(theta(t), t, 1)
(%i11) Assumption1: xdotdot(t)=0;
2
(%o11) r(t) cos(theta(t)) theta(t)    - r(t) sin(theta(t)) (theta(t) )
t t                               t
+ 2 r(t)  cos(theta(t)) theta(t)  + r(t)    sin(theta(t)) = 0
t                       t       t t
(%i12) solve(Assumption1, r(t));
sin(theta(t)) r(t)    + 2 cos(theta(t)) theta(t)  r(t)
t t                           t     t
(%o12) [r(t) = - -------------------------------------------------------]
2
cos(theta(t)) theta(t)    - sin(theta(t)) (theta(t) )
t t                          t
(%i13) Assumption2: ydotdot(t)=0;
2
(%o13) - r(t) sin(theta(t)) theta(t)    - r(t) cos(theta(t)) (theta(t) )
t t                               t
- 2 r(t)  sin(theta(t)) theta(t)  + r(t)    cos(theta(t)) = 0
t                       t       t t
(%i14) E1_1: subst(rdot(t), diff(r(t), t, 1), Assumption1);
2
(%o14) r(t) cos(theta(t)) theta(t)    - r(t) sin(theta(t)) (theta(t) )
t t                               t
+ 2 rdot(t) cos(theta(t)) theta(t)  + r(t)    sin(theta(t)) = 0
t       t t
(%i15) E1_2: subst(rdotdot(t), diff(diff(r(t), t, 1),t,1), E1_1);
2
(%o15) r(t) cos(theta(t)) theta(t)    - r(t) sin(theta(t)) (theta(t) )
t t                               t
+ 2 rdot(t) cos(theta(t)) theta(t)  + rdotdot(t) sin(theta(t)) = 0
t
(%i16) E1_3: subst(rr(t), r(t), E1_2);
2
(%o16) rr(t) cos(theta(t)) theta(t)    - rr(t) sin(theta(t)) (theta(t) )
t t                                t
+ 2 rdot(t) cos(theta(t)) theta(t)  + rdotdot(t) sin(theta(t)) = 0
t
(%i17) E1_4: solve(E1_3, rr(t));
2 rdot(t) cos(theta(t)) theta(t)  + rdotdot(t) sin(theta(t))
t
(%o17) [rr(t) = - ------------------------------------------------------------]
2
cos(theta(t)) theta(t)    - sin(theta(t)) (theta(t) )
t t                          t
(%i18) E1_5: subst(r(t), rr(t), E1_4[1]);
2 rdot(t) cos(theta(t)) theta(t)  + rdotdot(t) sin(theta(t))
t
(%o18) r(t) = - ------------------------------------------------------------
2
cos(theta(t)) theta(t)    - sin(theta(t)) (theta(t) )
t t                          t
(%i19) ```
Run Example
```numer:true;
(%o1)                                true
(%i2) sqrt(34);
(%o2)                          5.830951894845301
(%i3) ```
Run Example
```declare(m,integer);
(%o1)                                done
(%i2) factorial_expand:true;
(%o2)                                true
(%i3) epsilon(n,k):=(binomial(n,k)*gamma(3/2)/gamma(3/2-n+k)-(-1)^n*binomial(n-1,k-1)*n!/k!);
3
binomial(n, k) gamma(-)
2
(%o3) epsilon(n, k) := -----------------------
3
gamma(- - n + k)
2
n
(- 1)  binomial(n - 1, k - 1) n!
- --------------------------------
k!
(%i4) G(m):=-m*(4*m-3)/2;
(- m) (4 m - 3)
(%o4)                       G(m) := ---------------
2
(%i5) rat(epsilon(2*m,2*m-4)-G(m)*epsilon(2*m-1,2*m-4));
8         7          6          5          4          3
(%o5)/R/ (1024 m  - 8704 m  + 30976 m  - 59680 m  + 67036 m  - 43756 m
2
+ 15309 m  - 2205 m)/96
(%i6) epsilon(4,1)-G(2)*epsilon(3,1);
15
(%o6)                                 --
4
(%i7) epsilon(2,1);
(%o7)                                 - 1
(%i8) epsilon(2,0);
1
(%o8)                                 - -
4
(%i9) ```

Help for True